Explants sterilization through metal nanoparticles for in vitro mass propagation of Eugenia involucrata - Illamas Gallon, Fernanda; Roberto Diniz da Silva, Paulo; Czarnescki da Silva, Denise; Bisogno de Castro, Ferdinando; Marcos Stefenon, Valdir (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
An efficient method for the sterilization of explants is essential for the establishment of plant micropropagation. In this study we aimed to evaluate the efficacy of treatments using silver and gold nanoparticles as disinfectant agents of explants of Eugenia involucrata, in comparison to results from three other sterilization procedures. The sterilization procedure based on serial immersions in ethanol, sodium hypochlorite, and silver nanoparticles was quite effective, providing a very low proportion of explants contamination in nodal segments and apical buds of E. involucrata. The same protocol using gold instead of silver nanoparticles did not control fungi contamination of the explants. The immersion of explants in an in-house prepared solution of silver nanoparticles revealed to be an easy, cheap and efficient method for sterilization of nodal segments and shoot apices of E. involucrata, while the gold nanoparticles treatment was ineffective for controlling fungal contamination in this study.